2006
DOI: 10.1002/bem.20284
|View full text |Cite
|
Sign up to set email alerts
|

A literature review: The effects of magnetic field exposure on blood flow and blood vessels in the microvasculature

Abstract: The effect of magnetic field (MF) exposure on microcirculation and microvasculature is not clear or widely explored. In the limited body of data that exists, there are contradictions as to the effects of MFs on blood perfusion and pressure. Approximately half of the cited studies indicate a vasodilatory effect of MFs; the remaining half indicate that MFs could trigger either vasodilation or vasoconstriction depending on initial vessel tone. Few studies indicate that MFs cause a decrease in perfusion or no effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
92
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(98 citation statements)
references
References 66 publications
2
92
0
4
Order By: Relevance
“…18,19,21,31,42 Many studies have revealed that electromagnetic fields at a wide range of frequencies, activate certain cellular mechanisms, increase blood flow, and produce vasodilation of the vascular tone. 20,43 These mechanisms may be related to cellular survival activity, the vascular system, as well as inflammation process following the use of PEMF. On the other hand, an abnormal rhythmic activity between thalamus and cortex, along with a decrease in the velocity of blood flow through cerebral arteries (especially the middle cerebral artery), were observed on the affected hemisphere in migraine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19,21,31,42 Many studies have revealed that electromagnetic fields at a wide range of frequencies, activate certain cellular mechanisms, increase blood flow, and produce vasodilation of the vascular tone. 20,43 These mechanisms may be related to cellular survival activity, the vascular system, as well as inflammation process following the use of PEMF. On the other hand, an abnormal rhythmic activity between thalamus and cortex, along with a decrease in the velocity of blood flow through cerebral arteries (especially the middle cerebral artery), were observed on the affected hemisphere in migraine.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Electromagnetic fields also enhance vascular tonicity and velocity. 20,21 They stimulate ATP, mitochondrial enzymes synthesis as well as the anti-inflammatory process. 21,22 They also increase the rate of synthesis (turnover) of dopamine and serotonin, eventually reducing the alpha band of EEG.…”
Section: Introductionmentioning
confidence: 99%
“…Low frequency electromagnetic fields have been applied as treatment for some specific pathologic conditions like bone fractures, skin ulcers, migraines [12]. According to a report in 2004, effects of 0.2 T electromagnetic field on angiogenesis in chick chorioallantoic membrane was measured [9].…”
Section: Discussionmentioning
confidence: 99%
“…If true, this may be beneficial for the future clinical use of ELF-EMFs because the weak field used in our study (6-and 8 Hz, 1 mT, 10 V m À1 ) meets the guidelines of the International Commission on Non-Ionizing Radiation Protection. 24 The potent effects of static magnetic fields on BP have been linked to the nitric oxide pathway, the Ca 2+ -dependent pathway, the sympathetic nervous system (for example, baroreflex sensitivity and the actions of sympathetic agonists or antagonists) and the neurohumoral regulatory system (for example, production and secretion of angiotensin II and aldosterone), as reviewed by McKay et al 25 The precise mechanism by which ELF-EMFs might ameliorate hypertension is unknown; however, there are two hypotheses that may explain the effect. One potential hypothesis is that the effect of EMFs may be mediated by melatonin release.…”
Section: Discussionmentioning
confidence: 99%